Investigating Dunedin whistlers using volcanic lightning. Issue 13 (2nd July 2014) - Antel, Claire; Collier, Andrew B.; Lichtenberger, János; Rodger, Craig J.
Abstract Whistlers detected at Dunedin, New Zealand are an anomaly: there is little lightning around Dunedin's conjugate point yet whistlers appear in relatively large numbers. These surplus whistlers have consequently inspired investigations into their origins. Dunedin's lightning‐sparse conjugate point lies in the Aleutian Islands, a region populated with active volcanoes. Their presence has allowed us to perform a novel analysis: the correlation of whistlers to volcanic lightning. We report on our investigation, which successfully yielded the first observations of "volcanic whistlers." It was found that the single July 2008 Mount Okmok eruption had an impressive effect on the number of whistlers at Dunedin. The eruptions at Mount Redoubt in 2009 also caused a sporadic flow of whistlers in Dunedin.